The River In Senganan Village As A Source Of Ideas For The Creation Of Paintings - Kanta, Putu Aripta Dera; Setem, I Wayan; Yudha, I Made Bendi (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
This Independent Study TA thesis has the theme